Rifampicin resistance in Mycobacterium tuberculosis in Iran: a two-centre study - Bahraminia, F. (New Microbes New Infect, 2021)
Multidrug-resistant tuberculosis remains a challenge. In this study, we investigated the incidence of rifampicin (RIF) resistance in Mycobacterium tuberculosis in a large number of pulmonary specimens. A two-center study in Tehran, the capital of Iran, was performed with 6624 pulmonary samples of patients with tuberculosis (TB) who were subjected to detection of RIF-resistant TB by GeneXpert MTB/RIF assay between May 2014 and July 2018. Conventional drug susceptibility testing was performed to confirm the results. Xpert MTB/RIF identified a total of 96 positives for M. tuberculosis, of which 5 (5.3%) samples were found to be RIF-resistant TB. All RIF-resistant and sensitive isolates detected by GeneXpert were phenotypically confirmed by drug susceptibility testing. These results indicated that the Xpert MTB/RIF test can be used as a rapid diagnostic method and can potentially decrease the morbidity associated with diagnostic delay and mistreatment.